2021
DOI: 10.1016/j.cub.2021.01.075
|View full text |Cite
|
Sign up to set email alerts
|

Ancient relaxation of an obligate short-day requirement in common bean through loss of CONSTANS-like gene function

Abstract: Ancient relaxation of an obligate short-day requirement in common bean through loss of CONSTANS-like gene function Highlights d The common bean gene COL2 specifies global differences in photoperiod sensitivity d COL2 represses flowering and FT expression under noninductive (long-day) conditions d Independent sequential loss of COL2 and PHYA3 occurred in both domesticated lineages d Near fixation of col2 mutations implies an important role during Andean domestication

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
25
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 63 publications
0
25
0
Order By: Relevance
“…Well-documented examples are seen in the cereals, wheat and barley, where mutations in the Ppd and Vrn genes have adjusted photoperiod and vernalization sensitivity and have been linked to the expansion of these crops into northern Europe from south west Asia and Mediterranean regions ( Cockram et al , 2007 ). Similar adaptations are also seen during the evolution of legume crops, with a reduction in photoperiod sensitivity conferred by mutations in PRR3 , PHYA , E1 , and GI genes in soybean ( Glycine max ; Lin et al , 2021 ), PHYA3 and COL2 in common bean ( Phaseolus vulgaris ; Weller et al , 2019 ; Gonzalez et al , 2021 ), and ELF3 in pea ( Pisum sativum ), lentil ( Lens culinaris ), and chickpea ( Cicer arietinum ; Weller et al , 2012 ; Ridge et al , 2017 ), which have in each case contributed to expansion of their ecogeographical range.…”
Section: Introductionmentioning
confidence: 65%
“…Well-documented examples are seen in the cereals, wheat and barley, where mutations in the Ppd and Vrn genes have adjusted photoperiod and vernalization sensitivity and have been linked to the expansion of these crops into northern Europe from south west Asia and Mediterranean regions ( Cockram et al , 2007 ). Similar adaptations are also seen during the evolution of legume crops, with a reduction in photoperiod sensitivity conferred by mutations in PRR3 , PHYA , E1 , and GI genes in soybean ( Glycine max ; Lin et al , 2021 ), PHYA3 and COL2 in common bean ( Phaseolus vulgaris ; Weller et al , 2019 ; Gonzalez et al , 2021 ), and ELF3 in pea ( Pisum sativum ), lentil ( Lens culinaris ), and chickpea ( Cicer arietinum ; Weller et al , 2012 ; Ridge et al , 2017 ), which have in each case contributed to expansion of their ecogeographical range.…”
Section: Introductionmentioning
confidence: 65%
“…4a, d, Supplementary Figs. [22][23][24][25]. During domestication, these two alleles were retained and passed onto the landraces in this region (Fig.…”
Section: Discussionmentioning
confidence: 94%
“…Stepwise selection of different cis -regulatory variants in an FT homolog also occurred at different evolutionary times for local adaptation in maize 22 . A recent study also indicated that stepwise selection of a CONSTANS LIKE gene and a Phytochrome A gene facilitated the adaptation of common bean to high latitudes 23 . These findings suggest that the gradual selection of different genes or different alleles of one gene is a common strategy during crop evolution and adaptation.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Sh1 genes for seed shattering were under parallel selection during cereal crop domestication (Lin et al, 2012), and the major flowering time gene Hd1 experienced parallel selection during domestication in cereal crops (Liu et al, 2015). A parallel loss of photoperiod sensitivity occurred independently in two domesticated lineages through sequential loss of COL2 and PHYA3 function in common bean (Gonza ´lez et al, 2021). In addition, the domestication gene G orthologs controlling seed dormancy were selected in parallel in at least three crop species (soybean, rice, and tomato) from different families, likely representing the first domestication syndrome gene subject to parallel selection in independent crop families (Wang et al, 2018).…”
Section: Discussionmentioning
confidence: 99%